Oral treprostinil improves pulmonary vascular compliance in pulmonary arterial hypertension. (March 2022) - Khan, Akram; White, R. James; Meyer, Gisela; Pulido Zamudio, Tomas R.; Jerjes-Sanchez, Carlos; Johnson, Dana; Grover, Rob; Broderick, Meredith; Ousmanou, Aliou; Holdstock, Louis; Michelakis, Evangelos
Abstract: Oral treprostinil has been shown to improve exercise capacity and delay disease progression in patients with pulmonary arterial hypertension (PAH), but its effects on hemodynamics are not well-characterized. The FREEDOM-EV trial was a Phase III, international, placebo-controlled, double-blind, event-driven study in 690 participants with PAH who were taking a single oral PAH therapy. FREEDOM-EV demonstrated a significantly reduced risk for clinical worsening with oral treprostinil taken three times daily and did not uncover new safety signals in PAH patients. Sixty-one participants in the FREEDOM-EV trial volunteered for a hemodynamics sub-study. Pulmonary artery compliance (PAC), a ratio of stroke volume to pulmonary pulse pressure, significantly increased from Baseline to Week 24 in the oral treprostinil group compared with the placebo group (geometric mean 26.4% active vs. -6.0% placebo; ANCOVA p=0.007). There was a significant increase in cardiac output in the oral treprostinil group compared to the placebo group (geometric mean 11.3% active vs. -6.4% placebo; ANCOVA p=0.005) and a corresponding significant reduction in pulmonary vascular resistance (PVR) (geometric mean -21.5 active vs. -1.8% placebo; ANCOVA p=0.02) from Baseline to Week 24. These data suggest that increased compliance contributes to the physiological mechanism by which oral treprostinil improves exercise capacity and delays clinical worsening for patients with PAH. Graphical abstract: Image 1 Highlights: In FREEDOM-EV, oral treprostinil significantly reduced PAH clinical worsening risk. 61 FREEDOM-EV participants had hemodynamic data collected in an optional sub-study. Oral treprostinil improved pulmonary vascular resistance and cardiac output at Week 24. Pulmonary artery compliance (stroke volume/pulse pressure) predicts outcomes in PAH. Oral treprostinil taken TID improved pulmonary artery compliance at Week 24.